Characterisation of breathing and associated central autonomic dysfunction in the Rett disorder. Issue 1 (1st July 2001) - Julu, P O O; Kerr, A M; Apartopoulos, F; Al-Rawas, S; Engerström, I Witt; Engerström, L; Jamal, G A; Hansen, S
Abstract : AIM: To investigate breathing rhythm and brain stem autonomic control in patients with Rett disorder. SETTING: Two university teaching hospitals in the United Kingdom and the Rett Centre, Sweden. PATIENTS: 56 female patients with Rett disorder, aged 2–35 years; 11 controls aged 5–28 years. DESIGN: One hour recordings of breathing movement, blood pressure, ECG R-R interval, heart rate, transcutaneous blood gases, cardiac vagal tone, and cardiac sensitivity to baroreflex measured on-line with synchronous EEG and video. Breathing rhythms were analysed in 47 cases. RESULTS: Respiratory rhythm was normal during sleep and abnormal in the waking state. Forced and apneustic breathing were prominent among 5–10 year olds, and Valsalva breathing in the over 18 year olds, who were also most likely to breathe normally. Inadequate breathing peaked among 10–18 year olds. Inadequate and exaggerated breathing was associated with vacant spells. Resting cardiac vagal tone and cardiac sensitivity to baroreflex were reduced. CONCLUSIONS: Labile respiratory rhythms and poor integrative inhibition in Rett disorder suggest brain immaturity. Linking this to an early monoaminergic defect suggests possible targets for the MECP2 gene in clinical intervention. Exaggerated and inadequate autonomic responses may contribute to sudden death.